Does Motivation, Resistance to Change, Training and Competencies Still Affecting Employee Performance? - Wardati, Nabila Tsaniyah Kesuma; Maharani, Anita; Rahayu, Heffi Christya (Ilomata International Journal of Management, 2025)
This study aims to see the relationship between factors that are considered to play a role in employee performance. These factors are as follows: motivation, resistance to change, and training still play an important role in employee performance. In addition to these factors, this study also looks at competence as a mediator. The approach to this research is quantitative, and the respondents involved in this study are employees who work in a state-owned company that focuses on insurance. This study uses a quantitative approach with survey data collection, on employees who work in one of the state-owned companies that focus on insurance services in Indonesia, this research applied PLS-SEM approach. From the results of the data analysis test, it is proven that all hypotheses are proven. The implication of this study is that companies can encourage employees to have performance by providing motivation and encouraging employees to follow changes and conduct training.